Analisis Implementasi Kepemimpinan Transformasional Dalam Organisasi Mahasiswa - Harefa, Darmianus; Korengkeng, Yossy; Linda, Oktrin; Sahiundaleng, Karmila; Tangkere, Tesalonika; Lengkong, Febriela (Institut Agama Kristen Negeri Manado, 2024)
Leadership is a crucial element in human life, particularly in a social context. Transformational leadership plays a significant role in shaping the performance of its members. This leadership style has been shown to enhance the spirit and enthusiasm of organizational members. The method used in this research is descriptive qualitativewith a case study approach, allowing the researcher to explore phenomena in depth and systematically. This study references previous research titled